Residual axial capacity of concrete-filled double-skin steel tube columns under close-in blast loading - Li, Minghong; Xia, Mengtao; Zong, Zhouhong; Wu, Gang; Zhang, Xihong (Elsevier, 2022)
Concrete-filled double-skin steel tubes (CFDSTs) are comprised of two concentrically placed steel tubes with the annulus between the tubes filled with concrete. A number of researches have established the prospect of CFDST columns as ideal alternatives for conventional reinforced concrete (RC) columns subjected to extreme events such as earthquakes, fires and vehicular collisions. Since structural columns are the most critical axial load-bearing members in structures, after experiencing blast loading the residual axial strength of key columns is crucial in preventing catastrophic damage of structural systems. Current knowledge on the residual axial load-bearing performance of CFDST columns is very limited. This paper studies the post-blast performance of CFDST columns after subjected close-in explosions, where the residual axial load-bearing capacity of blast-damaged columns is quantified using a high-fidelity physics-based (HFPB) numerical modelling tool. CFDST columns are built in the nonlinear dynamic analysis program LS-DYNA and are comprehensively validated against experimental results in the aspect of column damage profiles and residual axial capacity of blast-damage columns. Extensive parametric studies are then carried out to investigate the effect of several key design parameters, i.e., charge weight, standoff distance, column diameter, nominal steel ratio, column height and axial load ratios, on the residual axial capacity of CFDST columns after subjected close-in blast loads. The results demonstrated good residual axial load-bearing performance of CFDST columns after subjected to close-in detonations of man-portable improvised explosive devices (MPIEDs). Based on the numerical analysis results, an empirical formula is derived to predict the residual axial load-bearing capacity of CFDST columns after experiencing close-in explosions. The proposed empirical formula can be utilized to quickly evaluate the vulnerability of close-in blast damaged CFDST columns.